Superconducting and magnetic properties of a new EuAsFeO0.85F0.15 superconductor - Dmitriev, V.M.; Omel`yanovskiy, O.E.; Ishchenko, L.A.; Khristenko, E.V.; Rybaltchenko, L.F.; Terekhov, A.V.; Zaleski, A.J.; Khlybov, E.P.; Kostyleva, I.E.; Sadakov, A.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2009)
Polycrystalline samples of a new superconducting EuAsFeO0.85F0.15 compound with critical temperature Tc = 11 K were prepared by solid state synthesis. Its electric and magnetic properties have been investigated in magnetic fields from 0.1 to 140000 Oe. Critical magnetic fields Hc1, and Hc2 were measured and hence the magnetic penetration depths l and the coherence length x have been estimated. The temperature dependence Hc2(T) exhibits clear hyperbolic – type behavior starting with the lowest fields. The data derived were used to estimate probable high Tc and Hc2 in compounds doped with rare-earths having smallatomic radii.